Quantifying the dynamics of light tolerance in Arabidopsis plants during ontogenesis. (14th July 2015) - Carvalho, Fabricio E. L.; Ware, Maxwell A.; Ruban, Alexander V.
Abstract: The amount of light plants can tolerate during different phases of ontogenesis remains largely unknown. This was addressed here employing a novel methodology that uses the coefficient of photochemical quenching (qP) to assess the intactness of photosystem II reaction centres. Fluorescence quenching coefficients, total chlorophyll content and concentration of anthocyanins were determined weekly during the juvenile, adult, reproductive and senescent phases of plant ontogenesis. This enabled quantification of the protective effectiveness of non‐photochemical fluorescence quenching (NPQ) and determination of light tolerance. The light intensity that caused photoinhibition in 50% of leaf population increased from ∼70 μ mol m −2 s −1, for 1‐week‐old seedlings, to a maximum of 1385 μ mol m −2 s −1 for 8‐week‐old plants. After 8 weeks, the tolerated light intensity started to gradually decline, becoming only 332 μ mol m −2 s −1 for 13‐week‐old plants. The dependency of light tolerance on plant age was well‐related to the amplitude of protective NPQ (pNPQ) and the electron transport rates (ETRs). Light tolerance did not, however, show a similar trend to chlorophyll a / b ratios and content of anthocyanins. Our data suggest that pNPQ is crucial in defining the capability of high light tolerance by A rabidopsis plants during ontogenesis. Abstract : We quantified the capacity of plants to tolerate high light exposure during ontogenesis. Non‐photochemical chlorophyll fluorescence quenching was found to be the key protective process against photoinactivation of photosystem II reaction centers. The accumulation of anthocyanins was not related to the light tolerance of the photosystem II reaction centers. The anthocyanin concentration correlated well with the concentration of hydrogen peroxide, suggesting their potential antioxidant function.